Antologia romana. - Benedetti, Lorenzo; Bigi, Daniela; Lambarelli, Roberto (Siena : Galleria Alessandro Bagnai, 2002)
Aquilanti, Andrea ; Basilè, Matteo ; Canevari, Paolo ; Casolaro, Gea ; Colazzo, Marco ; Dafni & Papadatos ; Fumasoni, Rossella ; Kirchhoff, Thorsten ; Malizia, Andrea ; Notte, Caterina ; Paris, Marina ; Pietrella, Federico ; Pintaldi, Cristiano ; Pontrelli, Gioacchino ; Salvino, Andrea ; Savini, Maurizio ; Tranquilli, Adrian
per kunstenaar : biog., ind. tent., gr. tent.
Italiaans
Antologia romana, Galleria Alessandro Bagnai, Siena, 2 marzo - 30 aprile 2002
boek
Keywords: Roma